Stable node-based smoothed extended finite element method for fracture analysis of structures. (November 2020) - Zhao, J.W.; Feng, S.Z.; Tao, Y.R.; Li, Z.X.
Highlights: An efficient method is proposed for fracture analysis of structures. Singular integration can be avoided owing to the strain smoothing technique. A stabilization term is also added to further improve the performance. Abstract: Based on low-order elements, a stable node-based smoothed extended finite element method (SNS-XFEM) is proposed for fracture analysis of structures in this study. For the proposed method, the problem domain is discretized using low-order elements, which can be easily generated for structures with complex shapes. The node-based smoothing domains are then generated to perform the strain smoothing technique, which can effectively avoid singular integration. The discontinuity caused by crack is modeled using enrichment functions and a stabilization term based on strain gradient is also taken into account to further improve the accuracy. Finally, some numerical cases are studied to fully investigate the performance of present method. The obtained results show that the proposed SNS-XFEM can perform much better than standard XFEM and NS-XFEM.